Ancient Angkor - Freeman, Michael, 1945-; Jacques, Claude (London : Thames and Hudson Ltd., 1999)
Guide to art and architecture of Angkor, extinct city, Cambodia.
Includes bibliographical references (p. 228) and index.
Keywords: Temples -- Cambodia -- Angkor (Extinct city); Architecture, Khmer -- Cambodia -- Angkor (Extinct city); Angkor (Extinct city); Angkor (Extinct city) -- Pictorial works; Cambodia -- Antiquities; Angkor (Extinct city) -- Buildings, structures, etc